PENINGKATAN KAPASITAS INSTALASI PENGOLAHAN AIR TAMAN PUSPITA CITRA RAYA PERUMDAM TIRTA KERTA RAHARJA KABUPATEN TANGERANG - Natasya Rachman, Cecilia
Clean water is a fundamental human necessity crucial for health, safety, and quality of life, making its provision crucial. Taman Puspita Water Treatment Plant serves as a primary source of clean water for the residents of Tangerang Regency. However, with population growth and development, the current capacity of Taman Puspita's water treatment facility is inadequate to meet the demand for clean water. Therefore, planning for the improvement of Taman Puspita's water treatment capacity is essential to ensure the availability of clean water for the community. Taman Puspita Water Treatment Plant operates under the supervision of Tirta Kerta Raharja Regional Water Company and is responsible for supplying water to the residents of Citra Raya housing area within the service area of Water Supply System (SPAM) 2. Currently, Taman Puspita facility uses raw water from the Cimanceuri River, with a total processing capacity of 60 liters per second distributed across 3 configurations, namely 30 liters per second and 2 units of 3 x 15 liters per second. Based on projections for the service area of Taman Puspita Water Treatment Plant, the current capacity is insufficient to meet the projected increase in demand, estimated to reach 170 liters per second by 2043. Additionally, the author's data reveals that the raw water has 8 parameters that do not comply with standards. Therefore, three proposed alternatives are presented: (1) increasing the facility's capacity by adding similar units at the Taman Puspita location, (2) meeting the capacity by optimizing unit usage with improvements according to design capacity and adding new units to meet water demand projections until 2043 at the Taman Puspita location, and (3) meeting increased capacity through the construction of a new water treatment facility at a different location from Taman Puspita. Considering land requirements, construction ease, operational and maintenance convenience, construction costs, and operational and maintenance costs, the second alternative is chosen as the preferred option. The designed Water Treatment Plant adheres to the existing unit configuration with changes such as dimension optimization, pipe size adjustments, and additional units, particularly in the filtration and sludge treatment units. To ensure continuous water supply during the upgrading process, construction for the designed WTP will be divided into 3 periods, with construction in 2024 for WTP B, 2028 for WTP C, and 2044 for WTP A. The financing for the upgrading project is divided into 2 periods, with the first period requiring IDR 520,232,947.50 for WTP B and IDR 683,152,157.98 for WTP C. The second period necessitates a capital expenditure of IDR 4,423,082,803.21. With a total projected income of IDR 279,452,636,745 over 20 years and estimated operational and maintenance costs of IDR 1,897,946,843.36, the Net Present Value (NPV) is IDR 125,903,212,096, and the Benefit-Cost Ratio (BCR) is greater than one, indicating the project's economic feasibility and financial value.